The Effect of Stress Testing on German Bank Efficiency - Uelner, Christopher Jens (2018)
This study analyses the effect of adverse stress testing conditions on the efficiency of German banks from all of Germany’s three banking groups. To this end, Stochastic Frontier Analysis is used to determine the cost X-efficiency levels of 20 German commercial, savings and cooperative banks, which were included in the 2014 EU-wide stress test, for the period 2014 to 2016. This is done by estimating the efficiency for a baseline scenario before macro-economic variables are assigned adverse values to simulate the effects of adverse economic developments on the efficiency of German banks. A comparison of both scenarios follows this to derive clearer insights into the effect of stress testing on bank efficiency. Bank efficiency is essential for banks, since they navigate a challenging environment of increasing competition from foreign banks and non-bank financial institutions, which is driven by swift technological innovation. The banking groups that comprise Germany’s Three Pillar banking system represent diverse ownership structures and face agency problems, which are likely to further affect bank efficiency. Efficient financial systems rely on investor confidence, facilitated by adequate financial regulation. The high capital requirements of the Basel III regulatory framework and the exposure of banks to adverse and unlikely stress is likely to reduce bank efficiency and consequently investor confidence. Thus, the significance of the German banking sector to the European and worldwide economy, makes analysing the effect of stress testing on German bank efficiency important. The empirical results of this study suggest that despite adverse conditions, the average cost X-efficiency of German banks rises marginally and remains high for all banking groups, which is in line with the 2014 EU-wide stress test. This means that German banks are resilient to adverse economic conditions.